Pengaruh Dow Jones Industrial Average, Deutscher Aktienindex, Shanghai Stock Exchange Composite Index, dan Straits Times Index Terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia (Periode 2010 – 2012) - Tamara, Shevanda Febrilia; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aimed to know and analyze the effect of Dow Jones Industrial Average, Deutscher Aktienindex, Shanghai Stock Exchange Composite Index, and Straits Times Index to Indeks Harga Saham Gabungan. The data used in this research are monthly data from January 2010 to December 2012. In this research, methods of data analysis used were multiple linear regression. The results of this research shows that simultaneously Dow Jones Industrial Average, Deutscher Aktienindex, Shanghai Stock Exchange Composite Index, and Straits Times Index affect the movement of Indeks Harga Saham Gabungan. But, partially only Dow Jones Industrial Average, Shanghai Stock Exchange Composite Index, and Straits Times Index that have significant effect to Indeks Harga Saham Gabungan. During the observation period, Dow Jones Industrial Average and Straits Times Index have a positive effect to Indeks Harga Saham Gabungan. While Shanghai Stock Exchange Composite Index have a negative effect to Indeks Harga Saham Gabungan. Keywords: Dow Jones Industrial Average, Deutscher Aktienindex, Shanghai Stock Exchange Composite Index, Straits Times Index, Indeks Harga Saham Gabungan